ANALISIS DEFORMASI WILAYAH SUMATERA BAGIAN SELATAN DAN SELAT SUNDA PASCA GEMPA 2020 DENGAN DATA GPS DAN INSAR - Anggara, Ongky
The island of Sumatra is located along the collision of two tectonic plates, namely the Sunda Plate and the Indo-Australian Plate which form several fault segments, making it an area with high tectonic activity in the world. Based on their seismic history, the southern part of Sumatra and the Sunda Strait has a history of significant magnitude earthquakes with high seismicity intensity and seismic gaps that can potentially produce large future earthquakes. In this study, we analyzed interseismic deformation in southern Sumatra and the Sunda Strait using GPS data and analyzed tectonic activity during the coseismic phase of the Bengkulu earthquake on August 19 2020 with inversion of GPS and InSAR data to determine the characteristics of the earthquake source and determine the distribution of stress due to the earthquake. The GPS data used is a continuous station from 2018 to 2020.6 to determine the amount of deformation at each station and the InSAR data uses Sentinel-1A to determine the deformation spatially. The interseismic deformation of the GPS velocity on the Indo-Australian plate to the northeast with a value of ~65 mm/year, where the velocity is slowed down in the subduction zone to ~20 mm/year, while in the eastern region of Sumatra it is more stable ~5 mm/year. The strain that occurs is dominated by a shortening pattern due to pressure from the subduction zone, but in the Sunda Strait there is shorthening and extension due to volcanic activity and the eastern part is more stable from the effects of deformation. In the interseismic phase, the energy accumulated in area A is Mw 7.33 with a return period of 200 years, the energy is Mw 8.87 and in area B is Mw 7.31 with a return period of 200 years, the energy is Mw 8.83. In the Sumatran Fault Zone the value of the slip rate in the Semangko segment is 14.5 ± 3 mm/year, in the Kumering segment is 14 ± 2 mm/year, and in the Sianok segment is 16.5 ± 4 mm/year. The coseismic displacement of the August 19 2020 earthquake occurred with a value below ~5mm, with the displacement not significant with the InSAR LOS Displacement range deformation with a value of ~-40 mm to ~40 mm. Based on the slip model, a seismic moment value of 4.58 × 1019 Nm is obtained, equivalent to Mw7.04. The 19 August 2020 earthquake with the mainshock triggered an aftershock Mw6.9 earthquake in an increased stress zone.